Factors influencing entrepreneurial intention: Focusing on individuals' knowledge exploration and exploitation activities - Saerom Lee; Min-Jeong Kang; Byung-Keun Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
With rapid changes in industrial environments, the role of start-ups and their initial attempts toward the market are regarded as critical initiates. To increase the number of young start-up entrepreneurs, it is important to understand the relationship between entrepreneurial intention and its antecedents. Drawing on the organizational learning theory, we adopt the concept of exploration and exploitation as mediating roles of entrepreneurial intention as individual-level perspectives. Additionally, we consider innovativeness, self-efficacy, and internal locus of control as antecedents of two learning activities. The results indicate that each learning activity successfully supports the entrepreneurial intention, which requires a complex decision-making process and long-term efforts. This research discusses practical implications and guidelines for entrepreneurship education programs further.
Keywords: 650; entrepreneurial intention; exploitation; exploration; innovativeness; internal locus of control; organizational learning; self-efficacy; young start-up entrepreneur